The non-inclusive nature of 'all inclusive' economics: Paradoxes and possibilities of the resort complex. (June 2020) - Zopiatis, Anastasios; Savva, Christos S.; Lambertides, Neophytos
Abstract: The 'All Inclusive' (AI) concept has revolutionized package hospitality services and captured the attention of many industry stakeholders. Scholars have mostly investigated AI from the marketing perspective, whereas the economic ramifications of this type of product, for both hospitality operators and local communities, are still a barren landscape. Using a mixture of quantitative analysis techniques, including a two-step cluster analysis and econometric modeling, the study aims to enhance our conceptual capital pertaining to the economic impact of AI for local communities. The study focuses on overall tourists' spending, both within and outside their accommodation, with expenditure segmented into seven study-specific categories that highlight the economic specificities of AI. Findings, of interest to industry stakeholders, revealed the problematic and ambiguous status of AI provision in Cyprus, whereas actions, espousing the principles of cluster theories, that could maximize the economic contribution of AI to local economies are suggested. Highlights: We investigate 'all inclusive' (AI) economics with specific reference to a small-island tourist destination. We introduce a typology of AI customers, according to their level of expenditure. We confirm the problematic contribution of AI to local economies. We reveal AI to be a paradox regarding the development of sustainable tourism. We explore the application of tourism clustering theories in the AI context.